First occurrence of Drosera cayennensis Sagot ex Diels (Droseraceae) in the white sand campinas of the lower Tocantins River, state of Pará, such support for the creation of new protected areas - Ferreira, Leandro Valle; Santos, João Ubiratan Moreira dos; Bastos, Maria de Nazaré do Carmo; Cunha, Denise de Andrade (Boletim do Museu Paraense Emílio Goeldi - Ciências Naturais, 2013)
The White-sand vegetation (campinas) of Amazonia are one of the most threatened and least protected vegetation types in the state of Pará by extraction of sand used in construction. White-sand vegetation occupies less than 2% of the Pará. The sandy soils poor in nutrients and harbour a high number of endemic species which can act as indicators of environmental quality. Among these species is Drosera cayennensis sagot ex diels (droseraceae), a carnivorous plant. In a survey held in the Herbarium of the Museu Paraense Emílio Goeldi, only seven records were found for Pará, most of which were located in the campinas municipality of the Vigia, that is currently in a poor state of preservation. The first occurrence of D. cayennensis in a campinas in good condition is reported in the municipality of Cametá in Pará. However, at present these campinas are being destroyed from sand extraction, a similar process that resulted in the destruction of the campinas in the municipality of Vigia. The discovery of D. cayennensis in campinas of the municipality of Cametá demonstrates the conservation importance of the area, and provides further justification for the creation of a new unit of conservation before the area is irreversibly impacted.